Penatalaksanaan Perioperatif Atresia Esofagus dengan Fistula Trakeoesofageal - Sari, Djayanti; Widyastuti, Yunita; Fauzi, Rizqi Ahmad (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2020)
Esophageal atresia with trachheoesophageal fistula occurs in 1 in 3,000 to 5,000 births. Esophageal atresia is often associated with other congenital anomalies like ventricular septal defects, patent ductus arteriosus or tetralogy of fallot. We reported a neonatal patient with esophageal atresia. Surgery was performed 2 days after being treated at the NICU. The operation lasted for 2 hours 25 minutes. The anesthetic technique is GA, semi open with Jackson Reese, ETT number 3, controlled breathing. The premedication was 0.1 mg atropine sulphate and 5 µg fentanyl, induction and maintenance were sevoflurane and O2, and with 1mg atracurium muscle relaxant. Postoperatively, patient was transported to the NICU in an intubated condition. The problems of anesthesia management on patients with esophageal atresia are evaluation of aspiration pneumonia, gastric overdistence, difficulty in ventilating the patient, the presence of other congenital abnormalities, and postoperative intensive care. Early recognition, prevention of aspiration, and immediate delivery to tertiary health care center will improve infant morbidity and mortality significantly.